The Influence of Intellectual Capital on Corporate Financial Performance: Professional Empirical Evidence - Aisyiah Hassany, Nur; Faizall Al Saud, Mohd (Inovasi Analisis Data, 2025)
Purpose – This study aims to investigate the influence of intellectual capital IC on corporate financial performance (CFP) of the financial services industry in Brunei. It explores what role human capital HC, structural capital SC, and relational capital RC play in delivering financial performanceDesign/methodology/approach – This research used Canonical Correlation Analysis CCA to help to analyze the relationships between components of IC HC, SC, RC and financial performance measures (ROA, ROE, EPS). The data of sample are sourced from financial reports and market performance record of the firms in Brunei.Findings – The outputs correlate compellingly to IC constituents with CFP, where HC confirms to be the major drive in the financial industry while RC displays a substantial involvement in the service sector. The results of canonical correlation confirmed that the first function explained a large amount of variance of financial performance in both sectors. Furthermore, the study emphasizes cross-sectional diversity across different sectors in terms of IC impact on financial outcomes.Originality/value – Contrasting previous research, this is an empirical study of Brunei's economy focusing on the sector-specific dimension of IC on financial performance. Furthermore, it promotes the application of CCA in IC related studies, providing a better perspective in the multivariate setting.Research Implications – The results highlight the need for firms in Brunei to improve their IC management strategies based on their respective industry. Using data from this study, policymakers and corporate leaders alike can enhance workforce development, promote relational networks and integrate structural capital investments to achieve consistent financial growth.